2016
DOI: 10.1016/j.ipej.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype guided characterization and molecular analysis of Indian patients with long QT syndromes

Abstract: BackgroundLong QT syndromes (LQTS) are characterized by prolonged QTc interval on electrocardiogram (ECG) and manifest with syncope, seizures or sudden cardiac death. Long QT 1–3 constitute about 75% of all inherited LQTS. We classified a cohort of Indian patients for the common LQTS based on T wave morphology and triggering factors to prioritize the gene to be tested. We sought to identify the causative mutations and mutation spectrum, perform genotype-phenotype correlation and screen family members.MethodsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…At the protein level, we also found that the variants in KCNQ1 often affected the transmembrane spanning domains similar to previous studies 9,17–19 . So far, there is no clear genotype–phenotype correlation for the variants reported in the KCNQ1 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the protein level, we also found that the variants in KCNQ1 often affected the transmembrane spanning domains similar to previous studies 9,17–19 . So far, there is no clear genotype–phenotype correlation for the variants reported in the KCNQ1 .…”
Section: Discussionsupporting
confidence: 89%
“…For variants detected in KCNQ1 , the c.1097A>G variant was remarkable since it was observed in 30% of our entire patients. This variant has been reported as isolated case reports associated with LQTS, mainly in Turkish patients 14–18 . Besides, ın a comprehensive study performed on 2500 unrelated LQTS patients, mainly from the USA, only one individual reported with c.1097C>G. Since the KCNQ1 c.1097G>A variant emerged as the major allele in our cohort, this has brought into mind the possibility of being a founder mutation for the Turkish population 14 .…”
Section: Discussionmentioning
confidence: 71%
“…Those with mutation in each of these particular gene have different clinical characteristics and are associated with different triggering events for arrhythmia as well as response to treatment [ 6 ]. There were reports on various gene mutation frequency in Asian countries [ [7] , [8] , [9] , [10] , [11] , [12] ]. From a previous study in Thai children, the ratio of LQTS patients who had cardiac events at rest or sleep appeared to be higher than those found in other Asian countries [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Note that we used the LQTS-like F351A mutant, because the LQTS mutant F351S did not generate any currents (Figure 1—figure supplement 1). However, during the review process of this manuscript a new LQTS mutation, F351L, was found (Vyas et al, 2016). The current and fluorescence of this LQTS mutant is very similar to the current and fluorescence of F351A (Figure 3—figure supplement 3), suggesting that our conclusions on the LQTS-like F351A is also relevant for the LQTS mutant F351L.…”
Section: Discussionmentioning
confidence: 97%